Understanding why guide dogs fail to meet their predicted qualification outcomes - Jones, Daisy (2016)
Guide dogs provide life changing mobility support and companionship for thousands of blind and partially sighted people. A proportion of dogs undertaking training to be guides will not enter work due to health or temperamental reasons. This work was designed to investigate the issues associated with the training of guide dogs and the processes around matching them with a client to form a successful working partnership, by focussing on factors that made partnerships successful or resulted in a failure of the dog to qualify. Study 1 was aimed at developing an understanding of Guide Dogs and highlighting areas where research would aid the organisation. It was clear that investigating a cohort of dogs that excelled within the training programme but were unsuccessful, and a further group of dogs who appeared to be mediocre throughout their training but formed a successful working partnership would provide a rich source of data. Study 2 used in depth case studies of 10 dogs which were created in a blinded manner using records of the dog’s behaviour, progress through training, and reports of matching of the dog with a client if the dog qualified. This study demonstrated that dogs which were predicted to be withdrawn but in fact qualified were matched well with their owner, and in some cases had received extra training input to resolve any behavioural issues. Whereas dogs that were predicted to qualify but were withdrawn from training, had either underlying unrecognised behavioural problems that became apparent after a specific event, or had underlying behavioural problems which were inaccurately thought to have been corrected. Notable within these groups was the use of the descriptive term ‘confidence’ to describe the reaction of the dog in specific circumstances. Study 3 examined, using a mixed-methods approach, the use of descriptive terms to refer to ‘confidence’ within the reports of dogs, written by Guide Dogs staff. A ‘confidence index’ was developed and was measured in a matched group of 70 withdrawn and 70 qualified dogs. The confidence index was numerically larger for qualified dogs than withdrawn dogs; however there was no statistical difference between the two groups. The studies presented within this thesis used both qualitative and quantitative methods and focussed attention on: (1) consistent use of behavioural terminology (2) early identification of behavioural problems (3) appropriate training intervention, and (4) careful matching of the dog with the needs and ability of the client. The investigations involved looking at dog’s behaviour and the bond between humans and animals from the perspective of those who know them best, their trainers and owners. The studies and their results all have the potential to improve the number of successful guide dog partnerships, and bridges the fields of research surrounding the human animal bond and the behaviour of dogs.